The Internet of Things - Aware Business Processes for Logistics in Enterprise: IOT Enabled Processes and Current Approach Limitations - Ahmed Muayad Younus (Genius Journals, 2021)
The Internet of Things is intended to bridge the divide between physical business processes and information technologies. Supply chain management is a significant application area that can benefit from the Internet of Things. When connected to physical objects, IoT technologies such as sensor networks transform supply chain objects into smart objects. These products are capable of capturing context data and providing representations of things to information systems. This enables process-aware information systems to monitor supply chain processes. Additionally, intelligent things can conduct portions of business processes. They may exchange data and make judgments based on business logic in dispersed contexts. However, this logic acts solely in accordance with predetermined behavior. Unexpected exceptions resulting from realworld occurrences necessitate dynamic process adaptation in process definitions and associated instances. We cover the major IoT technologies connected with automated assistance of logistics business processes in this study. Additionally, we highlight the primary constraints of the Business Process Execution Language in terms of supporting design and runtime updates to these processes via smart items, and we focus on one of these obstacles: Integration of IoT services into corporate processes via process modelling and orchestration.
Keywords: The Internet of Things; Business Processes; Logistics of Enterprise; Supply chain management